Factors behind Poor Mechanization in Rice Cultivation in Orissa - S.K. Nath; C. Satapathy (Journal of Agricultural Extension Management, 2025)
Orissa comprises of ten agro-climatic zones with a coast line of 420 kms. A major part of the land topography of the state is undulated being locked in mountains and hill s. The Bay of Bengal, present on the border of ten districts, has affected its cropping pattern to a great extent. The North-Eastern coastal plain zone covers four revenue districts. Its soil varies from alluvial to sandy loam to laterite type. Rice, jute, groundnut, mustard, green gram, black gram and vegetables are main crops raised in this ecosystem. Ricerice cropping pattern is followed in most irrigated areas. Rice - green gram, rice -black gram, ri ce-mustard, rice - groundnut and rice - vegetable are also practiced in some patches. Balasore is one among the four districts coming under this agro-climatic zone. All the 12 CD blocks of the district come under the North-Eastern coastal plain zone. Rice is the major crop cultivated here as per the district agricultural statistics, 2006. Of the total cultivated area of 250550 ha, 220830 ha is cultivated by rice only